An analysis on Learning Condition in Developing of Listening Comprehension Model by Using Social Media for English Students - Syofianis Ismail (J-SHMIC : Journal of English for Academic, 2020)
Learning a foreign language by using social media is getting important because it has great potential to support student-centered learning, as it is flexible, interactive, and content–rich in nature. This research was aimed to develop an English listening comprehension model by using Social Media You tube. A Research and Development methodology ADDIE was used: analyzing students’ and teachers’ needs, designing a new learning materials, Developing material, Implementing it in a group, and evaluating the existing learning materials, validating the learning materials by experts, revising learning materials, trying out the learning materials, and revising learning materials. It was found that the existing learning materials were not appropriate for the students’ characteristics and were not organized in a systematic way. Students and lecturers indicated that they appreciated enjoyable English language learning materials such as songs, stories and games using You Tube. Based on these findings a new model for developing materials was developed for English Listening Comprehension Program at the Islamic University of Riau.